From Satisfaction to Loyalty: Analyzing the Impact of Service Quality and Corporate Image in Islamic Banking - Risqi Putri Hidayati; Mustika Widowati; Atif Windawati (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to analyze the relationship between service quality, corporate image, customer satisfaction, and customer loyalty at Bank Syariah Indonesia (BSI) in Semarang, with customer satisfaction serving as an intervening variable. The study employs a quantitative approach using a survey method, involving 100 respondents selected through purposive sampling. Primary data were collected using questionnaires and analyzed through Structural Equation Modeling (SEM), including inner and outer model evaluations. The findings indicate that service quality has a significant effect on customer loyalty, whereas corporate image does not significantly influence loyalty. Furthermore, customer satisfaction successfully mediates the relationship between service quality and customer loyalty but does not mediate the relationship between corporate image and loyalty. These findings highlight that improving service quality plays a crucial role in enhancing customer satisfaction, ultimately strengthening customer loyalty. Therefore, BSI in Semarang must focus on optimizing service quality to improve customer experience and ensure long-term customer loyalty to the Islamic bank